Pengaruh Intellectual Capital Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening (Studi Empiris pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Rasendriya, Renata Ucca Regina; Diana, Nur; Fakhriyyah, Dewi Diah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research was conducted to determine the influence of Intellectual Capital on Company Value with Profitability as an Intervening Variable (Empirical Study of Banking Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2023). The sampling technique used purposive sampling by knowing the company value and proxied by Price To Book Value (PBV) and a sample of 40 companies was obtained. The data analysis method in this research is quantitative data analysis using a Causality design, using the PLS (Partial Least Square) path analysis method with SmartPLS 3. The results of the research show that the intellectual capital variable consists of Value Added (VA), Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), and Value Added Intellectual Coefficient (VAICTM). The Intellectual Capital variable has no effect on the Company Value variable. Meanwhile, the Intellectual Capital variable has an effect on the Profitability variable, while the Profitability Variable has no effect on the Company Value variable. Meanwhile, the Profitability variable does not mediate the influence of Intellectual Capital on Company Value.Keywords: Intellectual capital, company value, profitability